A6.10 Anti citrullinated peptides/proteins antibodies induce secretion of CCL5/rantes by fibroblast like synoviocytes. (13th February 2015) - Capecchi, R; Prediletto, E; Pratesi, F; Italiani, P; Puxeddu, I; Panza, F; Migliorini, P
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disorder, characterised by a progressive joint damage, caused by a cellular infiltrate localised in the synovia. In RA, fibroblast like synoviocytes (FLS) acquire an aggressive phenotype and contribute to joint destruction also producing a variety of pro-inflammatory cytokines. In the pathogenesis of RA a pivotal role is played by fibroblast like synoviocytes (FLS), that produce cytokines that perpetuate inflammation. One of the serological markers of RA are anti citrullinated protein antibodies (ACPA), a family of autoantibodies recognising a wide variety of antigens all characterised by the deimination of arginine into citrulline. Among the different citrullinated targets, ACPA can bind viral citrullinated peptides (VCPs) and histone citrullinated peptides (HCPs). Despite their strict association with RA, so far little is known about the role of ACPA in the pathogenesis of the disease. Objective: The aim of this work was to analyse the effects of anti VCPs and HCPs antibodies on in vitro cultured FLS. Methods: FLS from RA and non RA patients were isolated from synovial fluid and used for experiments at 4–5th passage. Anti-VCPs and anti-HCPs antibodies were purified by affinity chromatography from RA patients sera and IgG from normal subjects were used as control antibodies. Anti-VCPs and –HCPs antibodies were incubated on subconfluent FLS; cells and supernatants were recovered at different time points. RANTES protein was quantified in the supernatants by sandwich ELISA and RANTES gene expression was evaluated by RT-PCR. To investigate intracellular signalling after ACPA stimulation, specific MAP kinase, already known to be activated during CCL5/RANTES production, were studied. Results: Anti-VCPs and anti-HCPs from 5 RA patients induce RNA expression and secretion of RANTES from FLS as compared with normal IgG (p < 0.001). No differences were observed between RA and non RA FLS. FLS stimulation with ACPA seems to induce phosphorylation of ERK, JNK and p38. Conclusions: These results suggest a novel mechanism potentially involved in damage induced by ACPA, mediated by the production of RANTES in FLS. ACPA might play a role in activation and chemotaxis of T cells in synovial tissue with a perpetuation in inflammation and immune response. Studies are in progress to clarify the intracellular pathways implicated in the synthesis of RANTES induced by ACPA in FLS and to define the target of ACPA on FLS surface.